Lipid quantification in living microalgal cultures with digital holographic microscopy - Yourassowsky, Catherine; Theunissen, Renaud; Dohet-Eraly, Jérôme; Dubois, Frank (Frontiers in Photonics, 2024)
Large amounts of lipids are stored inside lipid droplets by some microalgae. Since these lipids can be used to produce nutraceuticals and biodiesel in a sustainable way, research is developing on fast non-destructive methods to quantify and monitor the amount of lipids within microalgal cultures. In this paper, we have developed with digital holographic microscopy a fast quantitative method to assess the evolution of the lipid content inside the diatom Phaeodactylum tricornutum living cells. The method uses a specific processing of recorded hologram sequences based on the refocusing capability in digital holographic microscopy. In representative samples of the culture, inside living cells, each lipid droplet volume is evaluated. In those experiments, for each sample, more than one thousand lipid droplets are automatically analysed from a sequence of one hundred recorded holograms. We have validated the method thanks to correlative quantitative phase contrast–fluorescence imaging and extrapolated it to larger calibrated spherical refractive particles, to demonstrate the flexibility of the method.